2020
DOI: 10.5694/mja2.50480
|View full text |Cite
|
Sign up to set email alerts
|

Non‐clinical eye care support for Aboriginal and Torres Strait Islander Australians: a systematic review

Abstract: Objectives To describe research into non‐clinical support eye health care for Aboriginal and Torres Strait Islander (Indigenous) Australians, the people who provide such care, and its impact on eye health outcomes. Study design Systematic review and qualitative analysis of peer‐reviewed research publications. Data sources Peer‐reviewed research articles published between January 2000 and July 2018 and included in MEDLINE/EMBASE, Web of Science, Informit, EBSCO (CINAHL and Anthropology Plus), or ProQuest Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…CBRs proposed that a disjuncture in cultural and clinical understandings of diabetic eye disease may be prevented with the introduction of specific Indigenous cultural brokerage roles; that aim to bridge cultural and language gaps, through a combination of interpreting, clinical appointment coordination assistance and family/community engagement. A non-clinical role such as this would support, rather than replicate the work performed by Indigenous health workers or eye health coordinators who are often overburdened by clinical and administrative responsibilities, limiting their capacity to provide cultural brokerage 28…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CBRs proposed that a disjuncture in cultural and clinical understandings of diabetic eye disease may be prevented with the introduction of specific Indigenous cultural brokerage roles; that aim to bridge cultural and language gaps, through a combination of interpreting, clinical appointment coordination assistance and family/community engagement. A non-clinical role such as this would support, rather than replicate the work performed by Indigenous health workers or eye health coordinators who are often overburdened by clinical and administrative responsibilities, limiting their capacity to provide cultural brokerage 28…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, Western biomedical understandings of health and illness place emphasis on identifying and treating standard disease entities within individual bodies, and tend to individualise the problem of poor health,32 despite widespread recognition that the social (and structural) determinants of health shape disease causation more than individual agency. The epistemological differences between these systems both directly and indirectly contribute to persisting poor eye health outcomes for Indigenous Australians 13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have also shown the superiority of peer encouragement in engaging patients, compared to encouragement from trained health professionals. 30 A recent review outlined the importance of non-clinical patient support from family members, carers and community liaison workers in increasing attendance at specialist care appointments 35 ; including escorting and sitting with patients while attending appointments, 36,37 and providing postoperative home care support like meal delivery. 38…”
Section: Eye Health Champions and Mutual Supportmentioning
confidence: 99%